Effects of one-dimensional migration of self-interstitial atom clusters on the decreasing behaviour of their number density in electron-irradiated α-iron. Issue 1 (2nd January 2020) - Abe, Y.; Satoh, Y.; Hashimoto, N.; Ohnuki, S.
ABSTRACT: An in- situ observation using high-voltage electron microscopy (HVEM) showed that the number density of stationary self-interstitial atom (SIA) clusters in electron-irradiated α -iron at room temperature seems to reach its peak value at an early stage of irradiation and continuously decreases at the prolonged irradiation. A thin foil specimen is used in the in situ HVEM experiments; hence, the SIA clusters can annihilate because of their escape to the specimen surfaces and their mutual coalescence through one-dimensional (1D) migration. In this study, we derive analytical models associated with the experimentally revealed 1D migration mechanisms to examine the decreasing behaviour of the cluster number density: (1) trapping of one-dimensionally migrating SIA clusters by impurity atoms within the specimen surfaces and (2) detrapping of stationary SIA clusters from a bounded impurity atom caused by impact with incident electrons. By introducing a simple cluster evolution model that accounts for only the trapping and detrapping processes, the model calculation indicates that the detrapping of the stationary SIA clusters causes the surface annihilation of the liberated SIA clusters, leading to the decrease in their number density. The decreasing behaviour is in closer accordance with the experimental data when setting the impurity concentration in the same order as the estimation from the previous in situ HVEM experiment. This result suggests that the trapping and detrapping of the SIA clusters are the possible underlying processes for the decreasing behaviour.